2016
DOI: 10.2151/jmsj.2016-012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Governing the Size Change of Tropical Cyclone-Like Vortices

Abstract: To understand the basic mechanism governing the size evolution of tropical cyclones (TCs), we systematically perform numerical experiments using the primitive equation system on an f-plane. A simplified, TC-like vortex is initially given and an external forcing mimicking cumulus heating is applied to an annular region at a prescribed distance from the vortex center. Moist process and surface friction are excluded for simplification. We focus on the sensitivity of size evolution to the location of the forcing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Clearly, the effectiveness of convection in producing inflow depends not only on its radial location, but also on its intensity and areal (including azimuthal) extent. It is therefore not surprising that cyclones in which deep convective rain bands extend relatively far from the circulation centre tend to have larger outer circulations compared with storms where deep convection is more confined, a feature demonstrated, for example, in the numerical simulations by Fudeyasu and Wang (2011) and in highly idealized simulations by Tsuji et al (2016). Nevertheless, the question still remains as to why there are areal differences in the distribution of convection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the effectiveness of convection in producing inflow depends not only on its radial location, but also on its intensity and areal (including azimuthal) extent. It is therefore not surprising that cyclones in which deep convective rain bands extend relatively far from the circulation centre tend to have larger outer circulations compared with storms where deep convection is more confined, a feature demonstrated, for example, in the numerical simulations by Fudeyasu and Wang (2011) and in highly idealized simulations by Tsuji et al (2016). Nevertheless, the question still remains as to why there are areal differences in the distribution of convection.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous theoretical attempts to account for the size differences between storms, including the size changes that may occur during the lifetime of an individual storm (DeMaria and Pickle, 1988; Xu and Wang, 2010; Smith et al , 2011; Chan and Chan, 2014; Frisius, 2015; Kilroy et al , 2016; Tsuji et al , 2016). Some of these studies have pointed to a monotonic relationship between the final size of storms and the size of the initial disturbance from which they form, a finding that motivates the present study in part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: a reduction of evaporative cooling in the outer rainbands (Sawada and Iwasaki 2010); cloud-radiative forcing (Bu et al 2014); changing the atmospheric temperature profile (Stovern and Ritchie 2016); and prescribing heating elements within certain rings around a vortex to mimic cumulus heating (Tsuji et al 2016). The main conclusions from these studies are essentially similar.…”
Section: Environmental Humidity and Convective Heatingmentioning
confidence: 94%
“…Previous studies suggested that numerous factors such as latitude, ocean basin, environmental pressure, relative humidity, the distribution of diabatic heating and sea surface temperature might affect TC size (Atkinson 1971;Merrill 1984;Frank and Gray 1980;Weatherford and Gray 1988;Cocks and Gray 2002;Liu and Chan 2002;Kimball and Mulekar 2004;Hill and Lackmann 2009;Chavas and Emanuel 2010;Chan and Chan 2012;Knaff et al 2014;Frisius 2015;Tsuji et al 2016;Sun et al 2017). For instance, Holland and Merrill (1984) found that the size of a TC was affected by its interaction with the environmental flow.…”
Section: Introductionmentioning
confidence: 99%